Smart classrooms, unheard perspectives: a global review of technology integration and local challenges in deaf and hard-of-hearing education in Saudi Arabia - Almulhim, Fatimah Abdullah (Frontiers in Education, 2025)
Background and objectivesInclusive education for deaf and hard-of-hearing (DHH) students, supported by digital innovation, has gained global prominence. However, their relevance to Saudi Arabia and Gulf countries has not been well explored. Therefore, this review specifically addresses how global educational technologies are integrated into DHH education and what challenges and opportunities arise in the Saudi and Gulf contexts.Methods and search strategiesThe author included peer-reviewed English-language articles published over the past 10 years (January 2016–April 2025). These studies involved DHH students in educational settings and focused on technology adoption, accessibility, teaching strategies, and inclusive tools, which form the core of this review. Relevant studies were identified using appropriate keywords in Scopus, Web of Science, Embase, the Saudi Digital Library, the Education Resources Information Center, and MedLine.Review findingsThis review identifies key technological categories, such as assistive devices, captioning systems, learning management platforms, and sign language tools, that support DHH learners. The successful adoption of these tools is hindered by several barriers, including infrastructural gaps, scarce Arabic language content, and insufficient teacher training. However, government initiatives and teacher-led, regionally adapted digital innovations, demonstrate the potential create meaningful change.ConclusionAs Saudi Arabia undertakes educational reforms under Vision 2030, this review provides a regionally grounded synthesis that draws on global literature while emphasizing local challenges, such as limited Arabic-language digital tools, infrastructure disparities, and teacher-training gaps in DHH education. Therefore, context-specific studies examining the effectiveness of educational technologies for DHH students in Saudi Arabia are needed.